2018
DOI: 10.3168/jds.2017-14209
|View full text |Cite
|
Sign up to set email alerts
|

Replacing human-edible feed ingredients with by-products increases net food production efficiency in dairy cows

Abstract: Global demand for food is increasing, and use of large amounts of potentially human-edible feedstuffs for dairy cows is an important concern. The present study examined whether feeding a by-product-based concentrate combined with high-quality grass silage to high-producing dairy cows affected feed intake and milk production compared with a conventional diet, as well as the effect on efficiency of human food production. In a changeover experiment with four 21-d periods, 24 dairy cows in mid-lactation were offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 33 publications
9
42
2
Order By: Relevance
“…For example, milk Lys secretion by cows fed CON1 was 291× greater than the amount of HE Lys consumed by those cows. In agreement with the current study, Karlsson et al (2018) described improved net production of several human-digestible amino acids (His, Ile, Leu, Lys, Thr, Trp, Val, Phe + Tyr) when replacing corn and soybean meal with by-products. Furthermore, the greatest improvement in net production of digestible amino acids was observed for Lys (Karlsson et al, 2018).…”
Section: Human-edible Nutrient Recoverysupporting
confidence: 92%
See 3 more Smart Citations
“…For example, milk Lys secretion by cows fed CON1 was 291× greater than the amount of HE Lys consumed by those cows. In agreement with the current study, Karlsson et al (2018) described improved net production of several human-digestible amino acids (His, Ile, Leu, Lys, Thr, Trp, Val, Phe + Tyr) when replacing corn and soybean meal with by-products. Furthermore, the greatest improvement in net production of digestible amino acids was observed for Lys (Karlsson et al, 2018).…”
Section: Human-edible Nutrient Recoverysupporting
confidence: 92%
“…As in the current study, Karlsson et al (2018) reported similar DMI and a marginal decrease (32.1 vs. 30.8 kg/d, P = 0.06) in milk yield when replacing cereal grains and soybean meal with sugar beet pulp and distillers' grains. In contrast, Pang et al (2018) fed cows a diet composed of grass silage with either a byproduct or grain concentrate and found a trend for decreased DMI (P = 0.06) for the group fed the by-product concentrate with no differences in milk yield.…”
Section: Dairy Cattle Productivitysupporting
confidence: 84%
See 2 more Smart Citations
“…These very high efficiencies are only achievable on diets high in forage. However, the results on FB-supplemented diets with human-edible efficiency of 84% is in agreement with Karlsson et al (2018) reporting an efficiency of 73% for a grass silage-based diet supplemented with cereal grain and soybean meal. They reported efficiencies up to 268% when dietary concentrates were constituted completely of by-products (RSM, sugar beet pulp, and dried distillers grains with solubles).…”
Section: Energy and Nitrogen Metabolismsupporting
confidence: 89%